Strengthening Qur’anic Education Through a Qur’an Waqf Program: A Participatory Community Engagement Model - Dian Nur Hanifah; Fadhilah Dzihni Larashati; Nur, Lintang Safriana; Naya Maylla Faiza; Muhammad Agung Trimono; Puput Fitriyan; Mukhammad Iqbal Ibrahim; Alfiatuz Zahra; Alvy Rahmawati; Azzahra Nabila Fitriyani; Putut Isna Riyana; Tiara Puspa Maharani; Anggi Prasetyo; Hibatulloh Rofiful Azmi; Zurotul Aeni; Resi Pratiwi (Lembaga Penelitian dan Pengabdian kepada Masyarakat UIN Prof. K.H. Saifuddin Zuhri, 2025)
The Program of Wakaf Kitabullah (WAFI) is a community service initiative aimed at improving the quality of Qur’anic learning facilities in Merbuh Village, Singorojo District, Kendal Regency. This pro-gram was developed based on observational findings indicating that several Qur’anic Learning Centers or Taman Pendidikan al-Qur’an (TPQ) in the village experienced shortages of mushaf, both in terms of quantity and physical condition, which hindered Qur’an reading and writing activities as well as stu-dents’ independent learning. The program was implemented using a participatory community en-gagement approach, involving university students participating in the Community Service Program, or Kuliah Kerja Nyata (KKN), Dompet Dhuafa Central Java, Gramedia Semarang Pandanaran, village au-thorities, and TPQ teachers. The activities included needs assessment, donation fundraising, a formal handover ceremony, and direct distribution of mushaf to five TPQs and one mosque. A total of 158 mushaf were successfully collected and distributed based on the level of need of each institution. The program’s impact was reflected in improved reading comfort and fluency, increased student learning motivation, and enhanced quality of instructional interaction. Moreover, the program strengthened social awareness, waqf culture, and community collaboration. The WAFI program demonstrates that multi-stakeholder synergy through a waqf-based scheme can make a significant contribution to im-proving the quality of Qur’anic education in rural areas.